Tensile hardness and wear properties of iron oxide (Fe3O4) reinforced aluminium 7075 metal matrix composites. Issue 4 (2nd October 2022) - a, Shivaramakrishna; Subramanya, Raghavendra; Basavaraj, Yadavalli
ABSTRACT: The Al-7075 aluminium alloy has been proposed for widespread use in automotive applications. This material has been researched in composite structures with various reinforcements in order to improve its usage. In this study, Fe3 O4 (magnetite) is reinforced in an Al-7075 matrix to create a metal matrix composite by a stir casting process. Aside from the Neat Matrix samples, five samples were produced by adding Fe3 O4 to Al 7075 matrix in various weight proportions such as 2, 4, 6, 8, and 10. The mechanical properties of the fabricated composite specimens were determined by different tests, including hardness, tensile, compression, and wear strength. The results were compared to a standard matrix alloy. In addition, SEM with EDAX studies was performed to examine the dispersion of the reinforced particles in the chosen matrix alloy. The homogeneous distribution of Fe3 O4 particles in composites was observed to be intragranular in origin. Furthermore, Fe3 O4 particles were found to be well attached to the matrix alloy, with a clean interface. The composite's hardness and tensile strength along with wear resistance were also found to increase as the Fe3 O4 concentration increased.